Analisis Faktor Dominan Dalam Pelaksanaan Sistem Pengendalian Intern Pemerintah Pada Satuan Kerja Keuangan Polda Aceh - Aliamin; Hendri Mauliansyah; Rachmad Fadhli (Asosiasi Dosen dan Praktisi Ekonomi Nusantara, 2025)
This study aims to find out what factors are the most dominant in the implementation of SPIP in the Aceh Police Financial Work Unit. This research includes quantitative research, with the data source using primary data obtained by distributing questionnaires. The data analysis technique uses Confirmatory Factor Analysis (CFA), with the results showing that there are 5 (five) factors/elements applied in the implementation of SPIP, namely the control environment, risk assessment, control activities, information and communication, and supervision. Among the five factors, only 3 (three) factors, namely the control environment, risk assessment, and control activities are dominant in the implementation of SPIP, while the other 2 (two) factors, namely information and communication, and supervision do not have dominance in forming a good and effective SPIP in the Aceh Police Finance Task Force.